Fabricação de eletrodo arame tubular auto protegido composto por tubo de aço carbono e fluxo contendo Fe-Cr-Ni para a formação de aço inoxidável como metal de solda na soldagem subaquática de aço carbono A36 - Maria Mariana Simões Ferreira (2020)
In Brazil, in recent decades, due to the great development of the oil industry, there has been a growing interest in underwater welding processes, motivated by the need to build and repair marine structures. Underwater welding is classified into three types: dry welding, local dry welding and wet welding. "Wet" process is the most commonly used and occurs directly in the aqueous environment without any piece of equipment that establishes barriers between the water and the region to be welded. It is usually performed by the Shielded Metal Arc Welding (SMAW) process, but its short electrode length limits its productivity. Flux cored arc welding (FCAW), therefore, it is an alternative to replace this process, since the wire is fed continuously without the need for electrode exchange, promoting increased process productivity. Self-shielded tubular wires are being used not only because of their ability to produce gases and slag that protect the melt pool, but also because of the possibility to add alloying elements, denitrifying and deoxidizing components that can modify the characteristics of the weld bead. However, the action of flow components does not totally eliminate the effects of the aqueous environment in which the process occurs. Hydrogen cracking, for example, is a common defect of welded joints under these conditions and leads to reduced mechanical strength and service life of welded components. Given the above, this work investigated the formation of a duplex stainless steel weld metal, since, compared to carbon steel, the microstructure of this material has higher resistance to bead corrosion, less tendency to cold cracking and solidification cracking. Experimental self-shielding tubular wires were fabricated in a wire drawing machine from an AISI 1006 carbon steel tube and flux containing nickel metal powder and iron-chrome alloy, which are key elements for the formation of duplex stainless steel. The microstructure identification was performed through the optical microscope, the ferritoscope and the phase quantification technique. Mechanical characterization was performed by Vickers microhardness profile survey. The chemical composition analyses of the weld metals were performed by the optical emission spectrometry technique. The alloy element content of the weld metal was significantly lower than the flux element content. The electrode with higher Ni content in flux composition formed duplex stainless steel in air welding. In underwater welding, electrodes with lower CaCO3 content and higher TiO2 content produced beads with better characteristics. In underwater welding of carbon steel there is a greater tendency for the formation of martensitic microstructure even with the use of consumables based on Ni and Cr.